#TITLE_ALTERNATIVE# - (NIM 23805008), HADI
Measurement of fluid property such as density, viscosity, and bulk modulus (K) has many developed. This research exploits ultrasonic method to determine density, viscosity, and bulk modulus of fluids. Sample of liquid is mixture between glycerin and aquadest with various compositions. This measurement is using ultrasonic transducers type MB4S-E with frequency 4 MHz. Result of measurement in the form of time delay and intensity, what can be changed to the speed of sound and coefficient of attenuation. As reference of result, the same sample is also measured in Lab. Chemistry ITB. Calculation can be solving by two ways, first theoretical formulation and second empirical equation. Theoretical way, have not good result. For density have mean error = 7.20% with RMSE = 93.5. Viscosity = 23.8% with RMSE = 12.8. Bulk Modulus = 7.26% with RMSE = 0.29. Best result is get empirically, for densities = 0.67% with RMSE = 8.74. Viscosity = 9.5% with RMSE = 2.44. Bulk Modulus = 2.35% with RMSE = 0.04.